2014
DOI: 10.1155/2014/205986
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Tribological Performances for Porous Structure of Diatom Frustule with FSI Method

Abstract: Tribological performances of the diatom frustule are investigated with the liquid-solid interaction (FSI) method. Take, for example, the representativeCoscinodiscussp. shell; the diatom frustule with the porous structure is achieved by the scanning electron microscope (SEM). Based on the frustule, the representative diatom frustule is modeled. Further, tribological performances of the diatom at its different geometry sizes and velocities are solved with FSI method and compared with corresponding values for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These pores were linked to the tribological performances of Coscinodiscus sp. (Meng et al, 2014). It was found that the modeled nanoporous diatom frustules exhibit increased load bearing capacity than the nonporous structure.…”
Section: Fe-sem Imaging Of Cyclotella Meneghinianamentioning
confidence: 95%
“…These pores were linked to the tribological performances of Coscinodiscus sp. (Meng et al, 2014). It was found that the modeled nanoporous diatom frustules exhibit increased load bearing capacity than the nonporous structure.…”
Section: Fe-sem Imaging Of Cyclotella Meneghinianamentioning
confidence: 95%
“…Meng et al (2014) investigated numerically the tribological performance of the diatom frustule using FSI method for different geometry sizes and velocities. A diatom is a single-celled organism, which is widely found in the sea-water or freshwater.…”
Section: Fluid-structure Interaction In Biomedical Applicationsmentioning
confidence: 99%